Paradigm shift from land redistribution to use of redistributed land for poverty alleviation and sustainable development in South Africa - Sihlangu, Precious (My University, 2021)
Access to land in South Africa has become a pressing concern and one that needs special attention. This is so despite the advent of democracy in 1994 which brought legislative frameworks and other measures promoting access to land. This study seeks to demonstrate the importance of accessibility of land to ensure realization of socio economic rights through productive use of land and consequently contribute to poverty alleviation and sustainable development in South Africa. The study examines adequacy of access to land and productive use of such land by evaluating the effectiveness of delivery of land reform program. The study emphasises that productive use of land should be strengthened in order to ensure acceleration of realization of sustainable socio-economic rights such as provision of food and better living conditions for land reform beneficiaries. The study further encourages the need to strengthen legislative measures and compliance in order to improve the delivery of post-settlement support services to land reform beneficiaries. The Legislation such as Restitution of Land Rights Act, Provision of Land and Assistance Act , Extension of Security tenure Act and Land Adjustment Act were promulgated and mainly aimed at addressing and regulating the allocation or distribution of land to persons or communities who were previously dispossessed of their land and further made provisions for instances where one or more persons claim ownership of land, but do not have registered title deeds in respect thereof, and to provide for incidental matters. There is a need for radical enforcement of laws, legislation, and regulations promoting access to land through restitution, redistribution and strengthening tenure reform in order to realize the delivery and enjoyment of socio-economic rights through productive use of land. This study reviews laws and regulations in an attempt to utilize land as a tool to alleviate poverty and accelerate sustainable development in South Africa, which will enable people to gain access to essential services particularly in rural areas. Therefore, there is a need to ensure that redistributed land is used productively to improve the lives of land reform beneficiaries
Thesis (LLD.) -- University of Limpopo, 2021
Keywords: Legislation; Poverty; Land; Access to land; Land reform; Socio-economic rights; Abandoned mined lands reclamation; Land reform; Bills, Legislative; Land reform -- South Africa; Sustainable development -- South Africa; Land reform beneficiaries